Potential of Bacteria from Alternative Fermented Foods as Starter Cultures for the Production of Wheat Sourdoughs - Comasio, Andrea (Microorganisms, 2020)
Microbial strains for starter culture-initiated sourdough productions are commonly isolated from a fermenting flour–water mixture. Yet, starter culture strains isolated from matrices other than sourdoughs could provide the dough with interesting metabolic properties and hence change the organoleptic properties of the concomitant breads. Furthermore, the selection of sourdough starter cultures does not need to be limited to lactic acid bacteria (LAB), as other food-grade microorganisms are sometimes found in sourdoughs. Therefore, different strains belonging to LAB, acetic acid bacteria (AAB), and coagulase-negative staphylococci (CNS) that originated from different fermented food matrices (fermenting cocoa pulp-bean mass, fermented sausage, and water kefir), were examined as to their prevalence in a wheat sourdough ecosystem during 72-h fermentations. Limosilactobacillus fermentum IMDO 222 (fermented cocoa pulp-bean mass isolate) and Latilactobacillus sakei CTC 494 (fermented sausage isolate) seemed to be promising candidates as sourdough starter culture strains, as were the AAB strains Acetobacter pasteurianus IMDO 386B and Gluconobacter oxydans IMDO A845 (both isolated from fermented cocoa pulp-bean mass), due to their competitiveness in the wheat flour-water mixtures. Wheat breads made with G. oxydans IMDO A845 sourdoughs were significantly darker than reference wheat breads.